Numerical study on variation in support reaction of skewed bridges - Madhavi, N.; Baskar, K. (Journal of Structural Engineering, 2025)
The major challenge in the highway bridges is providing a better alignment in the form of straightness in order to ensure a greater safety and speed. This creates the constriction of geometry, which indeed increases the demand of skewed bridges. The skew in the bridges makes the design very complicated and obscure. Though the skewed bridges are idealized through simple models, the actual structural behavior is highly erratic in nature and therefore, it is very much essential to study the bridges in detail to understand the complete behavior. A detailed numerical study is carried out with various parameters and the effect of skew angle on the support reaction is being highlighted. A Finite Element (FE) program is developed using MATLAB platform and is being used to carry out the skew bridge analysis under various parameter such as skew angles and bridge geometries. Parametric study is carried out on beam grid model under IRC-Class AA loading. From the parametric study, it is noted that the support reaction varies significantly with respect to varying skew angle between 0◦ and 60◦. An uplift reaction is also noticed at the acute corner with increase in skew angle. The variation is significant for skew angles more than 20◦. The variation in the support reaction with reference to the skew angle are discussed elaborately for four different loading cases such as Bending-Bending, Torsion-Torsion, Bending-Torsion, and Torsion-Bending.